2015
DOI: 10.1371/journal.pone.0135518
|View full text |Cite
|
Sign up to set email alerts
|

Economic Performance and Sustainability of a Novel Intercropping System on the North China Plain

Abstract: Double cropping of wheat and maize is common on the North China Plain, but it provides limited income to rural households due to the small farm sizes in the region. Local farmers in Quzhou County have therefore innovated their production system by integration of watermelon as a companion cash crop into the system. We examine the economic performance and sustainability of this novel intercropping system using crop yield data from 2010 to 2012 and farm household survey data collected in 2012. Our results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
4
35
0
2
Order By: Relevance
“…A school of thought concerning the resource use of intercropping systems states that a combination of two contrasting species, usually legumes/cereals, would lead to greater overall biological productivity than each species grown separately because the mixture can use resources more effectively than under separate monocultures [27]. Huang et al [28] explored how corn-faba bean, corn-soybean, corn-chickpea, and corn-turnip intercropping affected yields and nutrient acquisition in Chinese agricultural fields. The authors found that the intercropping systems more efficiently removed nitrogen from the soil -indicating increased resource use efficiency in the polycultures.…”
Section: Changes In Soil Biology and Crop Productivitymentioning
confidence: 99%
“…A school of thought concerning the resource use of intercropping systems states that a combination of two contrasting species, usually legumes/cereals, would lead to greater overall biological productivity than each species grown separately because the mixture can use resources more effectively than under separate monocultures [27]. Huang et al [28] explored how corn-faba bean, corn-soybean, corn-chickpea, and corn-turnip intercropping affected yields and nutrient acquisition in Chinese agricultural fields. The authors found that the intercropping systems more efficiently removed nitrogen from the soil -indicating increased resource use efficiency in the polycultures.…”
Section: Changes In Soil Biology and Crop Productivitymentioning
confidence: 99%
“…Annual-ryegrass grazed pastures, complemented by a double maizeBrassica or ryegrass rotation on 30% of the farm area, were estimated to lead to an operating surplus, combining with halving irrigated water use (Chapman et al, 2012). In northern China, wheat-maize double cropping has been innovated by intercropping watermelon with maize to get more than a 50% gross margin, though at higher irrigation and labor input, which should alleviate rural poverty in the region (Huang et al, 2015). In the Philippines, double cropping of rice in the wet season and maize in the dry season was feasible for reducing water use and increasing crop diversification and narrow rows with an intra-plant spacing of 50×20 cm had the highest biomass and grain yield for maize production among several plant geometries (Chauhan and Opeña, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These simple budgets are relevant because other budget components do not depend on the fertilizer input. The gross margin ( G ) was defined as the product of yield and price minus the fertilizer and seed and costs (Huang et al, ):G=Y×P-Cwhere Y is crop yield, P is the market price in the study area during the study period, and C represents costs of fertilizer and seed. For intercrops, G was calculated as:G=Ym×Pm+Yp×Pp-Cwhere indices “m” and “p” indicate maize and peanut, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These simple budgets are relevant because other budget components do not depend on the fertilizer input. The gross margin (G) was defined as the product of yield and price minus the fertilizer and seed and costs (Huang et al, 2015):…”
Section: Economic Performance Of Three Cropping Systemsmentioning
confidence: 99%